Knowledge management: an active intangible through research - Camilo Andrés Agudelo Vélez; Lina María Martínez Sánchez; Isabel Cristina Ortiz Trujillo (Universidad del Magdalena, 2014)
The knowledge management, is related to the management of the intangible assets that generate value for organizations. The majority of these intangible assets are present in related processes, of one form or another, with the acquisition, structuring and transmission of knowledge. Knowledge management is thus in formative research, an effective tool that comes from the understanding of the critical value of other factors, less "typical" that the documentation or the isolated data, and awareness of the need to find ways to sustain it and get this strategic benefits. For its part the research groups of research are spaces in which intangible assets of knowledge within university institutions, because the formative research embodied in the students, can generate a range of skills to facilitate scientific production.